2000
DOI: 10.1074/jbc.m002574200
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Calculation of pKReveals an Important Role of Arg205 in the Activity and Stability of Streptomyces sp. N174 Chitosanase

Abstract: Based on the crystal structure of chitosanase from Streptomyces sp. N174, we have calculated theoretical pK a values of the ionizable groups of this protein using a combination of the boundary element method and continuum electrostatics. The pK a value obtained for Arg 205 , which is located in the catalytic cleft, was abnormally high (>20.0), indicating that the guanidyl group may interact strongly with nearby charges. Chitosanases possessing mutations in this position (R205A, R205H, and R205Y), produced by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…S7A). This is consistent with studies of chitosanases OU01 and N174 (30,31). Trp-273 in AxMan113A provided a hydrophobic sugar-binding platform with the ϩ1 sugar ring.…”
Section: Structural Analysis Of Gh Family 113 ␤-14-mannanasesupporting
confidence: 90%
“…S7A). This is consistent with studies of chitosanases OU01 and N174 (30,31). Trp-273 in AxMan113A provided a hydrophobic sugar-binding platform with the ϩ1 sugar ring.…”
Section: Structural Analysis Of Gh Family 113 ␤-14-mannanasesupporting
confidence: 90%
“…This Arg ( R DP motif) is completely conserved in clan GH-J while the Tyr ( Y ASK motif) is not [28]. Similar findings have been reported before in another enzyme clan [29]. Based on all these findings, an improved catalytic mechanism is proposed within the GH-J clan.…”
Section: Introductionsupporting
confidence: 83%
“…Such residues can be involved in enzyme-substrate interaction, in structure stabilisation, but also in the creation of interaction networks essential for catalysis [6,11-13]. In CsnN174, examination of the microenvironment of the proton donor Glu22 revealed that this glutamate does not work independently but requires assistance from an interaction network involving three other residues (Arg205, Asp145 and Arg190) to achieve efficient catalysis [13]. Similar networks have also been observed in other members of the lysozyme superfamily, Bacillus circulans MH-K1 chitosanase (GH46), T4 lysozyme (GH24) and barley chitinase (GH19) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In CsnN174, examination of the microenvironment of the proton donor Glu22 revealed that this glutamate does not work independently but requires assistance from an interaction network involving three other residues (Arg205, Asp145 and Arg190) to achieve efficient catalysis [13]. Similar networks have also been observed in other members of the lysozyme superfamily, Bacillus circulans MH-K1 chitosanase (GH46), T4 lysozyme (GH24) and barley chitinase (GH19) [13]. In order to verify if a similar kind of interaction is needed to sustain the catalytic potential of the general base residue, we examined the microenvironment of Asp40 of CsnN174 and found that an arginine (Arg42) is highly conserved among the GH46 family of chitosanases.…”
Section: Introductionmentioning
confidence: 99%